EFEKTIVITAS KOMUNIKASI ORGANISASI PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI MALUKU - Zacharias, Tehubijuluw (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2019)
The aims of the research is to analyze the influence of variables of organization structure, technology, enviroment, communication pattern anda personal charasteristics on communication effectiveness.The sample was selected by using probablity sampling technicue with stratified random sampling method. The samples was determined based on sample table developed by Issac and Michael. Therefore, if the population were 303 people and confident level was 95%, the sample consisted of 189. The data were analyzed by using Structural Equation Modelling (SEM). The results of the research reveal that organization structure, technology, enviromet, communication pattern and personal charasteristics have a significant influence on organization communication effectiveness in Education, Youth and sports Departement of Maluku Province.Keywords: Structure;Technology;Enviromet;Communication Pattern; Personal Charasteristics